2013
DOI: 10.1080/09537325.2013.850476
|View full text |Cite
|
Sign up to set email alerts
|

Coopetition for radical innovation: technology, market and business-model perspectives

Abstract: Coopetition (collaboration between competing firms) is used in many contemporary industries to achieve various innovation-related benefits. However, there is still a lack of consensus in the existing literature as to whether it is beneficial in the case of radical innovations or whether it only supports incremental improvements due to the similarity of knowledge bases among competitors. We address this issue in an empirical study based on a cross-industrial survey in Finnish markets. The study focuses on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
120
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 64 publications
4
120
0
6
Order By: Relevance
“…Empirical studies addressing the impact of coopetition on radical and incremental innovation have reported contradictory results, which may be due to different dimensions of radicalness being measured (Ritala and Sainio 2014). Mention (2011, p. 51) found that coopetition has a negative influence on innovation novelty as firms are unwilling to share knowledge needed for such innovation and that coopetition "supports an imitation strategy rather than a willingness to introduce new to the market innovation".…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies addressing the impact of coopetition on radical and incremental innovation have reported contradictory results, which may be due to different dimensions of radicalness being measured (Ritala and Sainio 2014). Mention (2011, p. 51) found that coopetition has a negative influence on innovation novelty as firms are unwilling to share knowledge needed for such innovation and that coopetition "supports an imitation strategy rather than a willingness to introduce new to the market innovation".…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…Das and Teng 2000). The contradictory nature of coopetitive relationships can explain why research has been ambiguous about the effect of coopetition on innovative outcomes and, particularly, whether it is more beneficial for radical or incremental innovations Ritala and Sainio 2014). Fernandez et al (2014) argued that the challenges of coopetition require that firms manage tensions and adjust the relationship accordingly.…”
mentioning
confidence: 99%
“…Corporate sustainability demands to be free from the competitive view that the aim is to fight against rivals for market share within a given industry. Coopetition, a compound term of cooperation and competition, even appears in many contemporary industries [23,64,65]. The revolutionary mindset of cooperative competition starts with the recognition of sustainability-based strategies that most of one's own success can depend on the success of others [65,66].…”
Section: Corporate Sustainability Educationmentioning
confidence: 99%
“…Scholars have shown that coopetition can contribute to different types of innovation: incremental and radical innovation (Bouncken and Fredrich 2012;Yami and Nemeh 2014), open innovation (Enkel et al 2009;Chesbrough and Bogers 2014), and technological innovation (Ritala and Sainio 2014). Bengtsson and Kock (2000) and Osarenkhoe (2010) have found that cooperation is more important during the early phases of the innovation process, whereas competition is more important in the latter stages, namely when the firm has launched the product.…”
mentioning
confidence: 99%
“…The relation between coopetition and… Accordingly, some studies have begun to link coopetition to innovation (Ritala 2012;Bouncken and Fredrich 2012;Ritala and Sainio 2014;West and Bogers 2014;Yami and Nemeh 2014;Bouncken et al 2016). As innovation becomes further rooted in the organization's capacity to access external knowledge sources, coopetition increasingly shares a positive relationship with innovation, which offers a mechanism for organizational learning (Bengtsson and Kock 2000;Mas-Tur and Soriano 2014).…”
mentioning
confidence: 99%